Criticality Analysis for Research Vessel Machinery System Maintenance Strategy. Study Case: RV. Baruna Jaya - Muryadin Muryadin; Fariz Maulana Noor; Dimas Fajar Prasetyo; Rio Dwi Sakti Wijaya (Department of Naval Architecture - Diponegoro University, 2023)
In recent years, marine survey operations such as survey operations for underwater communication cables and tsunami early warning systems have become an annual activity involving research vessels in Indonesia. Along with the increasing age of the ship, it will be followed by a decrease in the performance of the machinery system. Maintenance of the machinery system is carried out to maintain the desired performance by ship users. However, with a large number of machinery system equipment and limited resources, an analysis is needed to prioritize which equipment or components need regular maintenance and monitoring activity. By classifying all assets into a hierarchical form and performing a risk-based criticality analysis, equipment will be prioritized based on the probability of failure and the level of consequence. By determining the probability of failure of a component based on historical data and reference failure data, and determining the consequences for health safety (HS), production (P), Environment (E), and Containment (Cn), the risk would be obtained. From this analysis obtained as many as 766 equipment and components consisting of 38 rotary equipment, 45 static equipment, 196 piping components, and 487 instruments. The risk analysis obtained as many as 23 (3%) of equipment in H (high), 138 (18%) in the M (medium) condition, and 605 (79%) in the L (low) condition. The criticality results determined that 161 (21%) equipment in H & L conditions would be carried out planned maintenance and 605 (79%) equipment in low condition would be carried out unplanned maintenance.